Computational Multiscale Modelling of Heterogeneous Material Layers - Hirschberger, C. B.; Ricker, S.; Steinmann, Paul; Sukumar, N (Engineering Fracture Mechanics, 2009)
A computational homogenization procedure for a material layer that possesses an underlying heterogeneous microstructure is introduced within the framework of finite deformations. The macroscopic material properties of the material layer are obtained from multiscale considerations. At the macro level, the layer is resolved as a cohesive interface situated within a continuum, and its underlying microstructure along the interface is treated as a continuous representative volume element of given height. The scales are linked via homogenization with customized hybrid boundary conditions on this representative volume element, which account for the deformation modes along the interface. A nested numerical solution scheme is adopted to link the macro and micro scales. Numerical examples successfully display the capability of the proposed approach to solve macroscopic boundary value problems with an evaluation of the constitutive properties of the material layer based on its micro-constitution.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-TM.comput_6